Christian Leadership Education for Youth through Social Organizational Communication Styles Based on Banyuwangi’s Local Culture in the Post-Pandemic - Suyanto, Richard Alejandre; Indrayani, Inri Inggrit; Goenawan, Felicia (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2025)
This study explored Christian leadership education for youth through organizational communication styles within a social institution, specifically, a church-based youth organization in Banyuwangi, Indonesia. The COVID-19 pandemic disrupted social interactions, leading to a significant decline in youth participation. However, post-pandemic observations revealed a notable increase in engagement among the youth members of GKT (Gereja Kristen Tuhan) Banyuwangi. This shift raised important questions about the role of leadership communication in revitalizing youth involvement. This study used a qualitative case study approach, data were collected through participant observation, interviews with four informants, and document analysis. The findings suggested that the youth leader employed varied communication styles depending on his social role within the organization. As a leader, he utilized controlling, structuring, and relinquishing styles; as a coach, he adopted a more directive approach; and as a teacher and peer, he favored an egalitarian style. These communication strategies, shaped by Christian values and local cultural norms of Banyuwangi, played a significant role in fostering motivation and participation among youth members.